The Characteristic of Parents and Elementary School Students in Offline Learning during The Covid-19 Pandemic in Indonesia - Hariati, Suni; Andriani, Andriani; Nurmaulid, Nurmaulid; Kadar, Kusrini S.; Erfina, Erfina (Faculty of Nursing, Universitas Hasanuddin, 2022)
Introduction: The government has issued a new policy to hold face-to-face meetings at schools in July 2021 following the decreased of positive confirmed cases of COVID-19 in children, increasing public discipline in health protocols implementation and most teachers have been vaccinated. However, the parents still worry about the spread of COVID-19 in school which creates anxiety for parents. Method: This study used a quantitative method with a cross-sectional survey approach. The population in this study were all parents of elementary school students (SD) in Indonesia. The sampling technique is non-probability sampling with a consecutive sampling approach where the researcher distributes the instrument online on social media. Data collection will be carried out in Sep – Nov 2022.Result: The majority of children who participated in offline learning were in grade 1-3 (76; 57.1%). The majority of education level of mothers (95; 70.9%) and fathers (95; 70.9%) were high education. Most of mothers (73; 54.5%) and fathers (103; 76.8%) had income more than three million rupiah. Most children participated in offline learning in July-December 2021 (85; 63.4%). Offline learning was held in 1-3 times a week (61; 45.5%) that occurs in 1-3 hours for day (68;50.7%). Conclusion: The implementation of offline learning is mostly held after June 2022, but there were several students who participated since 2020. There is variation of implementation offline learning from one to six days in a week